TREATMENT OF SCABIES AND CUTANEOUS SPOROTRICHOSIS IN DOMESTIC CATS USING IVERMECTIN AND SULFUR - Yulisa, Winda Ara; Jayanti, Putu Devi; Erawan, I Gusti Made Krisna (Buletin Veteriner Udayana, 2025)
Sarcoptes scabiei and Notoedres cati are parasites that cause scabies by burrowing tunnels under the epidermal layer of the skin. Sporotrichosis is a subcutaneous and systemic fungal infection in animals caused by Sporothrix spp. This case report aims to provide additional reference for the management of scabies and sporotrichosis cases. The case subject, a three-month-old female cat named Miya, exhibited itching, skin thickening, hair loss, and dandruff on several parts of the body, accompanied by decreased appetite since being adopted a week earlier. Physical examination revealed alopecia, hyperkeratosis, and scaling on the ear pinna and all four legs, as well as crusts and scales on the back, with a pruritus score of 7/10. Additionally, the mucous membranes of the eyes and mouth appeared pale. Supportive diagnostic tests using skin scraping detected the mite Notoedres cati. Cytological examination using the tape acetate preparation method revealed spore formations identified as Sporothrix spp. A complete hematological test indicated that the cat suffered from normocytic normochromic anemia. The treatment regimen included ivermectin injection, sulfur baths, the antihistamines diphenhydramine HCl and cetirizine, as well as supplements such as Sangobion and fish oil. After 14 days of treatment, hyperkeratosis, scaling, crusts, and flakes disappeared, though alopecia on the ear pinna remained. The cat’s pruritus resolved, appetite improved, and mucous membranes turned pink. The conclusion of this case report is that the 14-day treatment method proved to be effective in the recovery of the affected cat. In addition to effective treatment, maintaining a clean environment is recommended to prevent reinfection.